Experimental Study of the Thermo-Mechanical Properties of Building Blocks Used in Hot Desert Arid Climate - Hatia, Miloud; Kriker, Abdelouahed; Belatrache, Djamel (EAI Endorsed Transactions on Energy Web, 2020)
The desert areas in countries are characterized by their high heat, dry climate in summer and a very cold in winter. Currently, the building blocks used in the construction of slabs are found in concrete blocks, which are characterized by poor thermal performance. In the past, traditional gypsum was used to ensure that the stones used in the roof, which are shaped as domes, gave a significant thermal performance. In recent years, with the development of construction, other blocks have emerged in the market, such as scorched soil and polyester. The aim of this study is to determine the mechanical and thermal properties of the tested brick by laboratory experiments, as well as to make recommendations in line with the desert climatic conditions. The results show that the use of natural materials found in Sidi Khouield is highly efficient in reducing the internal temperature of studied houses. A maximal difference in the temperature between the inside and outside reaches 15 °C in P3.
Keywords: Palm fibers; gypsum blocks; concrete construction; thermal insulation